2019
DOI: 10.1111/ecin.12841
|View full text |Cite
|
Sign up to set email alerts
|

The Shifts in Lead‐lag Properties of the U.S. Business Cycle

Abstract: We document shifts in the lead‐lag properties of the U.S. business cycle since the mid‐1980s. Specifically, (1) the well‐known inverted leading indicator property of real interest rates has completely vanished; (2) labor productivity switched from positively leading to negatively lagging output and labor inputs over the cycle; and (3) the unemployment rate shifted from lagging productivity negatively to leading positively. Many contemporary business cycle models produce counterfactual cross‐correlations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(133 reference statements)
2
1
0
Order By: Relevance
“…This is consistent with Keynes' old argument and early empirical results surveyed inTaylor (1999). See also the discussion inMertens (2010) andBrault and Khan (2020).…”
supporting
confidence: 90%
“…This is consistent with Keynes' old argument and early empirical results surveyed inTaylor (1999). See also the discussion inMertens (2010) andBrault and Khan (2020).…”
supporting
confidence: 90%
“…More recently,Inoue et al (2020) propose a method for detecting and identifying misspecification in structural models and show that DSGE models can be severely misspecified.3 This is consistent with Keynes' old argument and early empirical results surveyed inTaylor (1999). See also the discussion inMertens (2010) andBrault and Khan (2020).…”
supporting
confidence: 54%
“…This can be achieved through a standard linear regression, by regressing the lead of the variables on its own current values and some lags. Brault and Khan (2018) used the new approach to calculate the business cycle synchronization in US for two periods (1947-1984 and 1985-2017). The use of the Hamilton filter has been criticized by some studies, it is suggested to use again the HP instead of the Hamilton filter (Astolfi, Chan, DE Quelioe, & Falasconi, 2019;Drehmann & Yetman, 2018).…”
Section: Currency Union After Crisismentioning
confidence: 99%